FAKTOR PENYEBAB KEBAKARAN HUTAN DI TAHURA SULTAN ADAM KALIMANTAN SELATAN - Sarah Damayanti Nasution; Fonny Rianawati; Susilawati Susilawati (Universitas Lambung Mangkurat, 2020)
The respondents were determined by purposive sampling while the respondents were calculated using Slovin formula. Determination of the location of the research was conducted based on Fire Insecurity Level (Suparni, 2014) with medium category in Tiwingan Lama Village and low category in Jorong Subdistrict. Based on the respondent's answer, the first cause of forest fires is land clearing 58%, the second is grazing and hunting with a percentage of 23%, the third is cigarette butt percentage 10%, the fourth by society that is not known cause percentage 9%. Factors causing forest fires in Tahura Sultan Adam by the first tourists are cigarette butts with a percentage of 64%, the second is the fire with a percentage of 25%, third is unknown cause percentage 11%. While in the District of Jorong which is included in the Tahura Sultan Adam area rarely there is human activity and road access is not adequate so that forest fires never happen.Keywords: Factors causing fire; Tahura Sultan Adam; Society and Tourists